Validation of Broth Macrodilution Volatilization Method for Testing of Essential Oils in Liquid and Vapor Phase: Chemical Composition, Cytotoxicity, and Antibacterial Effect of Indian Medicinal Plants against Pneumonia-Causing Pathogens - Chaure, Aishwarya; Houdkova, Marketa; Antih, Julien; Urbanova, Klara; Doskocil, Ivo; Naik, Mukund Lal; Patel, Khageshwar Singh; Kokoska, Ladislav (Molecules (Basel, Switzerland), 2023)
Essential oils (EOs) have great potential in inhalation therapy for the treatment of respiratory infections. However, innovative methods for evaluation of antimicrobial activity of their vapors are still needed. The current study reports validation of the broth macrodilution volatilization method for assessment of the antibacterial properties of EOs and shows the growth-inhibitory effect of Indian medicinal plants against pneumonia-causing bacteria in liquid and vapor phase. Among all samples tested, Trachyspermum ammi EO exhibits the strongest antibacterial effect against Haemophilus influenzae, with minimum inhibitory concentrations of 128 and 256 µg/mL in the liquid and vapor phases, respectively. Furthermore, Cyperus scariosus EO is found to be nontoxic to normal lung fibroblasts assessed by modified thiazolyl blue tetrazolium bromide assay. Chemical analysis performed using gas chromatography-mass spectrometry identified α-citral, cyperotundone, and thymol as the main constituents of Cymbopogon citratus, C. scariosus, and T. ammi EOs, respectively. In addition, β-cymene is identified as the major compound of T. ammi EO vapors when analyzed using solid-phase microextraction and gas-tight syringe sampling techniques. This study demonstrates the validity of the broth macrodilution volatilization method for antimicrobial screening of volatile compounds in the vapor phase and suggests the therapeutic potential of Indian medicinal plants in inhalation therapy.
Keywords: léčivé rostliny; Volatilization; pneumonie; Anti-Bacterial Agents; antiinfekční látky; volatiles; Anti-Infective Agents; respiratory infections; Cyperus scariosus; Trachyspermum ammi; Microbial Sensitivity Tests; Plants, Medicinal; MTT assay; headspace analysis; Cymbopogon citratus; GC/MS; Humans; Oils, Volatile; macrodilution; plynová chromatografie s hmotnostně spektrometrickou detekcí; antibakteriální látky; oleje prchavé; antimicrobial activity; volatilizace; mikrobiální testy citlivosti; Gas Chromatography-Mass Spectrometry; lidé; Pneumonia; vapor phase